PHYSICAL ANALYSIS OF QUALITY WOOD Melia azedarach - da Silva, T. J.; Barreiros, R. M.; Hansted, F. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Forest species, in general, present a slow growth, which results and profits can manifest themselves in the long run, it becomes necessary the study and discovery of new species that may provide raw materials and return on invested capital more immediate, being that the Melia azedarach wood is a potential option. In the absence of information about, the objective of this paper is to determine its physical properties: basic density and shrinkage of the Melia azedarach species in the Itapeva-SP region. The data obtained in this study allow to classify wood Melia azedarach as wood of average density and good dimensional stability. Feature that makes it ideal for its use in furniture industry. The low amount of research related to quality of this wood prevents the commercial use of it to achieve its full potential harnessing its effectively, and essential investments in this field.